Roberto Esposito New Directions in Biophilosophy - Rajan, Tilottama (Edinburgh University Press, 2022)
Internationally recognised scholars explore central themes and questions in Roberto Esposito's thoughtHelps scholars and readers of Esposito's work to understand the rich background that gives rise to and situates his bio-political worksIncludes an important new essay by Roberto Esposito himself that highlights the object of the his current philosophical focus: the outside of human thoughtProvides a rich critical assessment of Esposito's philosophical corpus, ultimately extending the philosophical debates launched by his workGathers leading international experts including Timothy Campbell, Olga Zorzi Pugliese and Gary Genosko This collection invites readers to reposition Esposito's thought and explore the interdisciplinarity and unique methodology of his whole corpus. It addresses Esposito's long-standing engagement with early modern philosophy, philosophy of biology, biopolitics, and the impolitical and the impersonal, together with his significant dialogues with contemporary philosophers like Gilles Deleuze, Jacques Derrida, Simone Weil, Jean-Luc Nancy and Maurice Blanchot. A new essay by Esposito himself reveals the importance of philosophical sources and ideas that condition his thinking, especially outside and beyond the dominant biopolitical interpretative framework that has come to mark his reception in the English-speaking world